The economics of solar PV self-consumption in Thailand - Tongsopit, Sopitsuda; Junlakarn, Siripha; Wibulpolprasert, Wichsinee; Chaianong, Aksornchan; Kokchang, Phimsupha; Hoang, Nghia Vu (Renewable Energy, 2019)
Declining prices of solar photovoltaic modules and consumers’ interest in green electricity production are driving the prevalence of electricity “prosumers” worldwide. Prosumers are electricity consumers who produce electricity for their own consumption, using distributed energy technologies including distributed solar photovoltaics (DPVs). Many jurisdictions around the world are adjusting to this changing energy landscape by reforming their policies to support self-production and self-consumption of electricity. This paper analyzes the economics of electricity self-consumption of DPV electricity in Thailand. Based on our study, we assess the feasibility of DPV self-consumption schemes for four customer groups. Among the three schemes assessed, (no compensation for excess electricity, net metering, and net billing), all customer classes are profitable and net metering offers the most customer benefits. However, we recommend net billing for policy adoption, not only because of its sufficient level of economic viability but also its flexibility in addressing broad stakeholders’ concerns. Our analytical approach captures in detail how DPV sizing relative to the load may be impacted by those compensation mechanisms. Our methodology can be replicated by countries that would like to develop or reform their national-level DPV self-consumption policies during an energy transition.
Created from Fastlane, Scopus look-up
Keywords: Distributed solar PV; Net billing; Net metering; Rooftop PV self-consumption; Solar economics; Thailand solar PV policy